2015
DOI: 10.15408/es.v6i1.1103
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pemahaman Konsep Dengan Keterampilan Berpikir Kritis Melalui Model Pembelajaran Treffinger Pada Mata Kuliah Fisika Dasar

Abstract: Salah satu model alternatif untuk memfasilitasi mahasiswa mencapai pemahaman dan keterampilan berpikir kritis yakni menerapkan model pembelajaran Treffinger. Penelitian ini bertujuan untuk mengetahui hubungan pemahaman konsep dengan keterampilan berpikir kritis mahasiswa melalui model pembelajaran Treffinger. Penelitian ini dilaksanakan di Jurusan Pendidikan IPA FITK UIN Syarif Hidayatullah Jakarta, mulai bulan September-November 2012.Desain yang digunakan dalam penelitian ini adalah one shot case study. Penel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
1
2
0
2
Order By: Relevance
“…This is in accordance with the research report of Sa'adah et al (2017) which found a link between critical thinking skills and concept mastery. Likewise with the research report conducted by Alatas (2014) which found a relationship (correlation)…”
Section: Draw a Conclusionsupporting
confidence: 74%
“…This is in accordance with the research report of Sa'adah et al (2017) which found a link between critical thinking skills and concept mastery. Likewise with the research report conducted by Alatas (2014) which found a relationship (correlation)…”
Section: Draw a Conclusionsupporting
confidence: 74%
“…Kontribusi tingkat berpikir kritis memiliki hubungan fungsional yang signifikan terhadap hasil belajar fisika dengan sumbangan sebesar 82,7% [11]. Mahasiswa yang memiliki keterampilan berpikir kritis dalam pembelajaran fisika dapat belajar untuk melihat situasi secara logis dan objektif, serta gejala sadar pembiasaan dirinya [12].…”
Section: Pendahuluanunclassified
“…Thus, the implementation of inquiry based-STEM learning encourages students to combine multiple ideas and is closely related to concept understanding [5]. STEM learning trains thinking skills and improves cognitive intelligence in connecting various facts or information with their prior knowledge through challenging project-making activities [22].…”
Section: Questionmentioning
confidence: 99%